2020
DOI: 10.3390/toxins12120770
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Botulinum Toxin Type A (BoNT-A) Treatment in Brazilian Patients with Chronic Post-Stroke Spasticity: Results from the Observational, Multicenter, Prospective BCause Study

Abstract: Botulinum toxin type A (BoNT-A) is an effective treatment for post-stroke spasticity; however, some patients cannot access treatment until ≥1 year post-stroke. This Brazilian post-marketing study (NCT02390206) assessed the achievement of person-centered goals in patients with chronic post-stroke spasticity after a BoNT-A injection. Patients had a last documented stroke ≥1 year before study entry and post-stroke upper limb (UL) spasticity, with or without lower limb (LL) spasticity. Patients received BoNT-A inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
(37 reference statements)
4
10
0
Order By: Relevance
“…Clinical outcomes at Week 6, as measured by mean GAS-T scores, for patients injected with aboBoNT-A (47.8) or onaBoNT-A (43.1), were broadly consistent with those reported in previously published studies [ 8 , 9 , 23 , 24 ]. The GAS-T score informs on the accuracy of goal setting.…”
Section: Discussionsupporting
confidence: 84%
“…Clinical outcomes at Week 6, as measured by mean GAS-T scores, for patients injected with aboBoNT-A (47.8) or onaBoNT-A (43.1), were broadly consistent with those reported in previously published studies [ 8 , 9 , 23 , 24 ]. The GAS-T score informs on the accuracy of goal setting.…”
Section: Discussionsupporting
confidence: 84%
“…The arborization patterns in the muscles were analyzed in relation to the vertical length of the muscle, which was divided into 5 parts. This division was based on previous studies that found botulinum neurotoxin to spread a few centimeters from the injection site [ 17 - 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Injection with botulinum toxin has been shown to improve shoulder function and reduce pain in an observational study of chronic poststroke spasticity. 9 However, no injection guidance for these muscles has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder muscles have been included in clinical trials of botulinum toxin for upper limb spasticity and have demonstrated improvements 2–8 . Injection with botulinum toxin has been shown to improve shoulder function and reduce pain in an observational study of chronic poststroke spasticity 9 . However, no injection guidance for these muscles has been suggested.…”
Section: Introductionmentioning
confidence: 99%